2019
DOI: 10.1080/1828051x.2018.1547126
|View full text |Cite
|
Sign up to set email alerts
|

The impact of feeding corn dried distillers grains with solubles on milk yield and composition in lactating Awassi ewes and digestibility and N partitioning in Awassi ewe lambs

Abstract: The effect of corn dried distillers grains with solubles (DDGS) on milk yield, milk composition and body weight (BW) and digestibility were evaluated by using lactating ewe (Exp. 1) and Awassi ewe lambs (Exp. 2). Dietary treatments were (1) no DDGS (CON), (2) 200 gkg À1 DDGS (DDGS200) or (3) 300 gkg À1 DDGS (DDGS300) of dietary dry matter (DM). In Exp. 1, 30 lactating Awassi ewes were randomly assigned to the corresponding diets. Nutrient intakes were determined daily throughout the experiment which lasted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
4
19
0
Order By: Relevance
“…All animals completed the experiment without any noticeable health problems or disorders. In agreement with our results, previous studies have shown that the use of AF did not affect the health status of the animals [6,7,8,9,10]. In the current study, no effect on DM, CP, and ADF intake was found.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All animals completed the experiment without any noticeable health problems or disorders. In agreement with our results, previous studies have shown that the use of AF did not affect the health status of the animals [6,7,8,9,10]. In the current study, no effect on DM, CP, and ADF intake was found.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, BW change and ADG of nursing Awassi ewes and their lambs did not differ between treatment diets with 100, 150, and 200 g/kg DM of BB [16]. Alshdaifat and Obeidat [9] reported no impact on BW change of nursing ewes or ADG of their suckling lambs by replacing soybean meal with DDGS. Morricall [23] also found no difference in the BW of ewes and lamb total gain when nursing ewes were fed DDGS diets compared to basal diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a beneficial impact was observed when BCM was included at 53 and 106 g/kg in diets of growing calves [ 8 ], when included at 125 g/kg in lambs and calves diet [ 7 ], when included at 350 g/kg in camel diet [ 21 ] or when included at 50 or 100 g/kg in rabbit diets [ 22 ]. In agreement, other studies reported the economic impact of using agro-industrial by-products in feeding livestock [ 3 , 14 , 23 ]. In addition to these beneficial effects, the use of BCM and other oil cakes as alternative feeds in livestock diet would diminish environment pollution compared to if they were wasted [ 4 ].…”
Section: Discussionsupporting
confidence: 88%
“…Feeding, sampling procedure, and chemical analysis were carried out as described by Alshdaifat and Obeidat [9]. Briefly, feed refusals were weighed, recorded, and sampled to accurately measure nutrient intakes.…”
Section: Methodsmentioning
confidence: 99%